SAN LUIS POTOSIECTROPHOTOMETRY OF THE ORION NEBULA I ON THE NEBULAR STRUCTURE - MENDEZ, ME (UNAM, Observatorio Astronómico Nacional, CD MEXICO, DF, MEX, 1970)
Results of spectrophotometry observations of the Orion Nebula in the wavelength range ? 3600 - 11000 Å are presented. Apparent emission line intensities in various areas of the Huyghenian region have been corrected for interstellar and internebular extinc
BOL OBS TONAN TACUB
Keywords: SPECTROPHOTOMETRY, ORION NEBULA, NEBULAR STRUCTURE; ASTRONOMIA Y ASTROFISICA; ASTRONOMIA OPTICA; FOTOMETRIA